How does Social Media influence the Behaviour of Hotel Consumers? - Pontes, Alexandra; Ramos, Célia M. Q. (Journal of Tourism, Sustainability and Well-being, 2023)
People have easy access to the internet, social media and the information there. In just a matter of seconds, the consumer can obtain information about accommodation in any part of the world, including advertising and reviews. This research investigates social media in hospitality by analysing its effects on consumer behaviour: accommodation booking in the digital environment. Data were collected from Portuguese tourists spending holidays between 2018 and 2020 using a questionnaire shared on social networks. A structural equation model was employed to test the relationships among variables. The results show that advertising and the quality of testimonials shared on social media influence consumer behaviour when booking hotel accommodations. The more positive the comments on the online review sites, the more influence they have on consumer behaviour.